Condiciones del santuario nacional de calipuy para desarrollar un producto turístico rural comunitario - Canchachi Utrilla, Cindy Katherine (2016)
The purpose of this study is to identify the conditions that have the Santuario Nacional de Calipuy to develop a community-based rural tourism product; for which I have developed the following research: the Santuario Nacional de Calipuy space is a holder of a wide range of fauna with representative species such as white-tailed deer, Andean fox, Vizcacha, mountain partridge and cute Chinese; the most representative flora species is the Puya Raimondii called living fossil to have a lifespan of 80 to 100 years old, also we found medicinal plants like plantain, dog walking, valerian, among others. Complementing is also the presence of rock formations for adventure sports activities followed with bird watching, flora and fauna. On the other hand the population of the villages in the buffer zone of Quiguir and now Cusipampa to retain their traditional agricultural practices, in developing the various stages of production accompanied rustic use of tools developed by the same people; as support all these activities is the intention of women in collaboration with the Head of home care variety of domestic livestock and assistance in the field. Also, within each community it is social organizations that allow better distribution of roles; one of them is the support committee and monitoring the SNCA, who is responsible for supporting staff Guardaparque in patrols, reinforcement of fences, participation in workshops on the management and conservation of ANP. Important activities since it contributes to a more responsible hand of the participant population protection; within these organizations we find community leaders interested in entering small businesses with handicrafts (fabrics) made with traditional techniques Loom, Maychaque, callhua and conventional techniques sticks and developed crochet motifs to the Santuario Nacional de Calipuy in flora, wildlife and landscape. The investigation of each of these activities allows a community rural tourism product in the space investigated in accordance with the guidelines established by the MINCETUR for the development of this new type of tourism in Andean areas is implemented.